Elderly Attitudes on the Continuity of Working Careers - Vilkoitytė, Violeta; Skučienė, Daiva (Socialinė teorija, empirija, politika ir praktika, 2020)
This article analyses the elderly attitudes on the continuity of working careers in different sectors of the labour market. It discusses theoretical approaches and the determining factors of older people participation in the labour market. Attention is drawn to the impact they have in different labour market sectors. The investigation was carried out in primary quantitative data analysis. The factors of participation in different labour market sectors were analysed using the data of the European Working Conditions Survey (2015). Primary data are treated with the statistical software package (SPSS). Data analysis includes frequency distribution, cross-tabulation, chi-square tests, factor analysis, and logistic regression methods. The research results shown that in Lithuania, three quarters of the elderly want to pursue a professional career, but attitudes vary across sectors. Logistic regression models showed that job and health satisfaction is particularly important for all sectors. Gender is important in agriculture, hotels, and education. In the financial, public administration, education and health services, the role of education plays an important role and increases the attitudes of working longer. Harmful factors identified during the study had an impact on four branches. Psychologically challenging conditions have affected the financial and educational sectors, harmful substances and physically demanding working conditions affect the attitudes of workers in the manufacturing sector, and harmful feelings affect the agricultural sector workers.